PENGAWASAN IZIN USAHA TOKO MODERN (IUTM) OLEH DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA PEKANBARU (STUDI KASUS: RITEL ALFAMART DAN INDOMARET) - Mia Ayu Sukmawati; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Modern retail business is growing rapidly in line with the economic progress of Pekanbaru city. The rapid development of modern retail is contrary to the obligation of business actors to take care of their permits. To overcome these problems need to do supervision by the Department of Trade and Industry Pekanbaru City. The purpose of this research is to know the supervision of Modern Store Business License (IUTM) by Trade and Industrial Service of Pekanbaru City (Case Study: Retail Alfamart and Indomaret) and to know the factors that influence it. The theoretical concept used is the supervision by Brantas, is the monitoring steps include: Define the standards, measure the implementation, compare the results with the standards, take corrective action. This research uses qualitative method with case study approach. Technique of collecting data through interview technique, observation and documentation by using purposive sampling method in informant selection. The results show that Supervision of Modern Store Business License (IUTM) by Trade and Industry Office of Pekanbaru city (Case Study: Retail Alfamart and Indomaret) in its implementation have been good enough to be seen from indicator to determine standard, measure implementation, compare result with standard, running as it should but not optimal due to the factors that influence the human resources are still considered insufficient to oversee all areas of trade, then coordination between the Department of Trade and Industry Pekanbaru, Department of Investment and Services One Door of Pekanbaru City, and the Police Force of Pekanbaru Municipal Police less than optimal, and the low awareness of business actors to manage the Modern Store Business License (IUTM). Keywords: Supervision, Modern Store Business License (IUTM), Retail